Analysis of Role Clarity on Employee Performance through Organizational Commitment and Jobsatisfaction and at the Artificial Insemination Center Singosari Malang Regency - Nurhanani, Anjar Dyah; Anwar, Muhadjir (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to investigate the influence of role clarity on employee performance, considering organizational commitment and job satisfaction as moderating variables within the environment of the Balai Besar Inseminasi Buatan (BBIB) Singosari, Malang Regency. A quantitative approach with a causal associative design and a path analysis model was used to assess the relationships between variables. The primary objective is to identify the direct and indirect effects of independent (exogenous) variables on dependent (endogenous) variables. Data were analyzed using Partial Least Squares (PLS) with SMART PLS software, including tests for both the outer and inner models. Research findings indicate that role clarity not only directly enhances employee performance but also strengthens organizational commitment and job satisfaction, which in turn contribute to overall performance improvement.